Challenges in the development of new therapies for bronchiectasis. (April 2015) - Chalmers, James D; Loebinger, Michael; Aliberti, Stefano
Abstract : Introduction: Bronchiectasis is a neglected condition for which there are no licensed therapies. Increasing recognition of the disease has led to a surge in interest over recent years, with a number of active drug development programmes. Areas covered: Disappointing results with therapies successful in cystic fibrosis (CF) have forced a re-evaluation of how we develop new treatments for bronchiectasis. Bronchiectasis presents a unique array of challenges. These include a heterogeneous and poorly characterized patient population, a lack of agreed standards of care and a lack of understanding of the natural history. Pre-clinical development is limited by the lack of an adequate animal model of disease, and by our limited understanding of pathogenesis. There is no agreement on how to define key clinical trials end points including exacerbations and quality of life. The difficulty in translating positive Phase II data into successful Phase III trials suggests the need for better early phase trial end points. Expert opinion: Extrapolating from CF and chronic obstructive pulmonary disease has been a necessity but now risks holding back development if we do not recognize the unique challenges in bronchiectasis. This article comprehensively reviews the barriers to new drug development for bronchiectasis.